The Effect of Acupressure Wristband Therapy on Stress Levels Among Third-Trimester Pregnant Women - Marliana Rahma; Dewi Rubi Fitriani; Rina Dwi Anggraeni; Santi Komala Dewi; Siti Suniatuz Zahra (Jurnal Kesehatan dan Kedokteran, 2025)
Stress during pregnancy is a common psychological condition that may negatively affect maternal well-being and pregnancy outcomes. Persistent stress can increase the risk of anxiety, sleep disturbances, emotional instability, and adverse maternal and fetal health outcomes. Therefore, safe and non-pharmacological interventions are needed to help pregnant women manage psychological stress during pregnancy. This study aimed to determine the effectiveness of acupressure wristband therapy in reducing stress levels among third-trimester pregnant women. This study employed a quantitative approach using a quasi-experimental one-group pretest-posttest design. The study was conducted at TMPB Bidan Yayat Haryatini and involved 30 third-trimester pregnant women selected through purposive sampling. Stress levels were assessed before and after the intervention using a structured stress questionnaire. Participants were instructed to use an acupressure wristband positioned at the P6 (Nei Guan) acupressure point according to the intervention protocol. Data were analyzed using descriptive statistics and paired sample t-test analysis at a significance level of 0.05. The results showed that the mean pretest stress score was 60.83 ± 3.270, while the mean posttest stress score decreased to 42.43 ± 2.932. Statistical analysis demonstrated a significant difference between pretest and posttest stress scores (mean difference = 18.400; t = 202.261; p < 0.001). Participants also reported feeling more relaxed, experiencing reduced anxiety, improved sleep quality, and greater emotional comfort following the intervention. The findings indicate that acupressure wristband therapy is effective in reducing stress levels among third-trimester pregnant women. This study contributes empirical evidence supporting the use of wearable complementary therapies as a practical, safe, and non-pharmacological intervention in maternal healthcare. The results may serve as a basis for integrating acupressure wristband therapy into antenatal care programs to support maternal psychological well-being.